Experimental assessment of the performance and exhaust emissions characteristic of a diesel with jatropa curcas-ceiba pentandra mixture biodiesel/bioethanol blends - Sutrisno J.; Dharma S.; Silitonga A.S.; Shamsuddin A.H.; Sebayang A.H.; Milano J.; Rahmawaty; Supriyanto (Bangladesh University of Engineering and Technology, 2023)
The depletion of world oil reserves currently positively impacts the development of biofuels such as biodiesel and bioethanol, as this fuel is a renewable and environmentally friendly alternative and is considered to have enormous potential to supply energy needs. The purpose of this research is to investigate the performance and exhaust emissions from single diesel direct injection diesel engine which is fueled by biodiesel-bioethanol-diesel. Biodiesel was obtained from a mixture of Jatropa curcas-Ceiba pentandra crude oil with each composition being 50% produced by degumming process, acid catalyzed esterification, and alkaline-catalyzed transesterification. Biodiesel-bioethanoldiesel fuel is mixed in several conditions ie B10BE5, B20BE8, B30BE10, B40BE13, and B50BE15. In general, engine performance for low blend of biodiesel and bioethanol is close to diesel, for some engine parameters such as engine torque, brake power, and brake thermal efficiency. The addition of biodiesel and bioethanol into diesel fuel also has implications for reduced carbon emissions and smoke opacity. Overall, based on test results it can be concluded that the biodiesel-bioethanol mixture in low concentration in diesel fuel qualifies as an alternative fuel in diesel engines. 2020 Zibeline International Publishing Sdn. Bhd.. All rights reserved.